Near Frattini subgroups of residually finite generalized free products of groups - Mohammad K. Azarian (International Journal of Mathematics and Mathematical Sciences)
Let G=A★HB be the generalized free product of the groups A and B with the amalgamated subgroup H. Also, let λ(G) and ψ(G) represent the lower near Frattini subgroup and the near Frattini subgroup of G, respectively. If G is finitely generated and residually finite, then we show that ψ(G)≤H, provided H satisfies a nontrivial identical relation. Also, we prove that if G is residually finite, then λ(G)≤H, provided: (i) H satisfies a nontrivial identical relation and A,B possess proper subgroups A1,B1 of finite index containing H; (ii) neither A nor B lies in the variety generated by H; (iii) H<A1≤A and H<B1≤B, where A1 and B1 each satisfies a nontrivial identical relation; (iv) H is nilpotent.